Color stability of composites: effect of immersion media. - Borges, Alexandre L S; Costa, Anna K F; Saavedra, Guilherme S F A; Komori, Paula C P; Borges, Alessandra B; Rode, Sigmar M (My University, 2011)
Coloring in drinks decreases the color stability of composite restorations, reducing their longevity. The purpose of this in vitro study was to evaluate the effect of immersion media on color stability of seven different composite resins (Solidex - Shofu, Resilab-Wilcos, Signum - Heraeus, Epricord - Tokuyama, Adoro - Ivoclar Vivadent, Admira - Voco and Sinfony - 3MESPE). Seven resin-based composite specimens were prepared using a cylindrical teflon mold 2 mm thick and 10 mm in diameter Fifteen specimens of each resin were light-cured according to manufacturers' instructions and randomized into 3 groups (n= 5) according to immersion media: coffee, cola beverage and water A digital spectrophotometer Easy Shade (VITA) was used to evaluate the color changes at baseline and 7 days after immersion in each solution. Specimens were stored in the different staining media for 24 h/day during one week. The color differences were analyzed by two-way ANOVA and Tukey 's test (p< 0.05). Color change was observed after one week of immersion and there were statistical differences in staining, composite and interaction factors. The least staining was observed in Admira (deltaE= 3.934+/-0.814) and Resilab (deltaE= 3.993+/-0.735), followed by Adoro (deltaE= 4.044+/-1.001), Epri-cord (deltaE= 4.049+/-1.234), Signum (deltaE= 4.260+/-1.785), Solidex (deltaE=5,122+/-0.534) and Sinfony (deltaE=5.126+/-0.838). All of the composites tested except Adoro were susceptible to staining by substances present in coffee and cola, when stored in beverage for seven days. The lowest deltaE means were obtained with Admira.
Keywords: resin; color; immersion; materials testing; Color; Composite Resins; Immersion; Materials Testing